The influence of the investment factor on the transformation of the global energy market - Rudkovskyy, Serhii (Technology audit and production reserves, 2020)
The object of the study is the transformation of the world energy market under the influence of investment. The study of the impact of investments on the transformation of the world energy market was carried out in terms of market, structural, and organizational parameters in the following areas: – the growing role of renewable sources in the world energy balance; – liberalization of sectoral energy markets; – wide application of information technologies, including the introduction of Smart Grid at various levels. The main disadvantages are the inability to analyze the transformation processes in all sectors of energy at the global level. Such general scientific and special methods as methods of analysis and synthesis, method of comparative analysis, graphic and statistical methods were used in the research. The paper shows that at the present stage the main prerequisite for investment has been the COVD-19 pandemic and pre-crisis expectations. This has led to a sharp decline in global investment in all energy sectors (both in aggregate energy supply and in end-use) and in research and development. In terms of industry, investments in oil and oil products (by all organizational forms of companies) and coal decreased the most. Investment in electricity and electricity networks exceeds investment in mining and processing of fossil fuels. The main factors holding back international investment in renewable energy are: – relatively lower economic and energy return on investment (EROI); – the high cost of connection to power systems; – local component requirements and other protectionist requirements; – discrediting by global oil and gas corporations about the danger of economic downturn and job cuts, etc. In the regional structure, the largest volumes of global investment are in the Asia-Pacific region, North America, and Europe. Insufficient investment in the accelerated transformation of the world energy market on the basis of sustainable development has been stated in all areas. The targeted efforts of both national governments and the international community are needed to ensure the desired transformation of the global energy market.